Skopos and (Un)certainty: How Functional Translators Deal with Doubt - Nord, Christiane (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
There are no rules for translation. Translation is a decision-making process, and each decision point involves uncertainty. In the following article, I would like to show how, from a skopos-theoretical perspective, a top-down procedure can at least reduce uncertainty to some degree. The top level is that of the translation brief, which determines the choice of translation type and form. This is a binary decision. A documentary translation usually “documents” the pragmatics of the source text, whereas an instrumental translation gets a pragmatics of its own, for example with regard to deixis. At the next level, the translator has to deal with cultural norms and conventions. Here, the decision becomes more complex because the brief may require the reproduction of some source-culture behaviours and the adaptation of others to target-culture conventions, both in documentary and instrumental translations. The next level is that of language. We may safely assume that most translations are expected to conform to the norms of the target-language system, but there may be cases where source-language norms have to be reproduced, for example in an interlinear translation for linguistic purposes. At the last two levels, the remaining doubts have to be resolved first in line with contextual restrictions and, ultimately, the translator’s personal preferences, if necessary.